Biosorption of pulp and paper mill effluent by Emericella nidulans: isotherms, kinetics and mechanism. Issue 47 (7th October 2016) - Singhal, Anjali; Jha, Pawan Kumar; Thakur, Indu Shekhar
Abstract: In this study, a fungus, Emericella nidulans (anamorph: Aspergillus nidulans ), isolated from the sediments of a drain carrying effluent of pulp and paper mill, was used for biosorption of colour from pulp and paper mill effluent. The fungus turned dark brown in colour after treatment. Thus, its biosorption potential was studied in detail. The surface of the fungus was characterized by SEM and FT-IR analysis. The effect of change in pH, temperature, inoculum's size, contact time and initial concentration on colour adsorption was studied. The equilibrium data were studied using Freundlich, Langmuir, Elovich and Temkin equations. Best fitting model was Freundlich, used to describe heterogeneous systems. The pseudo-first-order and pseudo-second-order were used to fit adsorption data in the kinetic studies. The results showed that kinetics was best described by pseudo-second-order model. A detailed error analysis was undertaken. The mechanism of biosorption was governed by both external mass transport and intraparticle diffusion. The negative value of Gibbs energy change (Δ G °) indicates that the process was feasible and spontaneous. The value of activation energy ( E a ) showed chemical adsorption, and positive value of isosteric heat of adsorption (Δ H r ) indicated that the process was endothermic. Adsorbents capable of removing pollutants from waste stream are widely applied in treating wastewater.